Changes of the characteristics of Satureja hortensis L. herb during flowering period - Héjja, M.; Héthelyi, É.; Ferenczy, A. Z.; Szentgyörgyi, E. (International Journal of Horticultural Science, 2001)
In this study the changes of the characteristics of Satureja hortensis herb were investigated during flowering period, in case of savories of 4 different origins. The change of drying ratio, leaf/stem ratio, essential oil content, the ratio of several essential oil components (carvacrol, y-terpinene, p-cymol, a-pinene, p-pinene and fi-caryophyllene) were studied from bud formation till seed ripening.